2022
DOI: 10.1073/pnas.2118793119
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum chaperone BiP is a closure-accelerating cochaperone of Grp94

Abstract: Hsp70 and Hsp90 chaperones provide protein quality control to the cytoplasm, endoplasmic reticulum (ER), and mitochondria. Hsp90 activity is often enhanced by cochaperones that drive conformational changes needed for ATP-dependent closure and capture of client proteins. Hsp90 activity is also enhanced when working with Hsp70, but, in this case, the underlying mechanistic explanation is poorly understood. Here we examine the ER-specific Hsp70/Hsp90 paralogs (BiP/Grp94) and discover that BiP itself acts as a coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…The ATPase activity of GRP94 is relatively low, indicating that GRP94 requires a co-chaperone to enhance its binding to the designated clients 23,45 . Recent studies have shown that BiP is a novel interacting partner of GRP94, and that BiP assists with the acceleration of the closure of GRP94 to trap the client protein 22 . However, there is a lack information on which co-chaperones might act with ENPL-1/GRP94 for proinsulin handling and processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ATPase activity of GRP94 is relatively low, indicating that GRP94 requires a co-chaperone to enhance its binding to the designated clients 23,45 . Recent studies have shown that BiP is a novel interacting partner of GRP94, and that BiP assists with the acceleration of the closure of GRP94 to trap the client protein 22 . However, there is a lack information on which co-chaperones might act with ENPL-1/GRP94 for proinsulin handling and processing.…”
Section: Discussionmentioning
confidence: 99%
“…GRP94 requires BiP for the accelerating the closure of its open state and trapping the proIGF2 client protein. The slow ATPase activity 23 and the slow closure of GRP94 22 suggest that it requires other chaperones to assist in its conformational changes which are required for binding its client proteins. Clients bind via the defined client binding CBD while the regions of GRP94 required for co-chaperone association are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the role of CNPY3 has been suggested to support the loading of TLR proteins onto GRP94, indicating for the first time that an ER luminal chaperone requires help from other chaperones to fulfil its function. The other well-described chaperone of GRP94 is BiP ( Huang et al, 2022 ; Jansen et al, 2012 ; Jin et al, 2021 ; Sun et al, 2019 ). GRP94 requires BiP to accelerate its open state and for trapping the proIGF2 client protein.…”
Section: Introductionmentioning
confidence: 99%
“…GRP94 requires BiP to accelerate its open state and for trapping the proIGF2 client protein. The slow ATPase activity ( Frey et al, 2007 ) and the slow closure of GRP94 ( Huang et al, 2022 ) suggest that GRP94 requires other chaperones to assist in the conformational changes that are required for its binding to client proteins. Clients bind via the defined client-binding domain CBD but the regions of GRP94 required for the co-chaperone association are unknown.…”
Section: Introductionmentioning
confidence: 99%